The Effect Of Corporate Social Responsibility (CSR), Growth Opportunity, And Company Characteristics On Earning Response Coefficient (Case Study On The Conventional Banking Sector Listed On The Indonesia Stock Exchange-IDX 2018-2022) - Tasya Nabila, Amelia; Paramita, V. Santi (International Journal of Science, Technology & Management, 2024)
Earnings Response Coefficient (ERC) is one of the measures used to measure earnings quality. Earnings Response Coefficient (ERC) is a valuation model that can be used to indicate the possibility of rising and falling stock prices for market reactions to earnings information announced by the company. By knowing the factors that affect the Earnings Response Coefficient (ERC), information can be obtained about how strong the market reaction is to the earnings information presented by the company. This study aims to examine and analyze the effect of Corporate Social Resposibilty, growth opportunity and company characteristics on earning response coefficient in conventional banking sector listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 period. This research belongs to quantitative research. The sampling technique used purposive sampling technique, 43 conventional bank used as a population with 11 conventional bank companies is used as a research sample. The analysis method of this research used panel data regression analysis. The results showed that: (1) CSR has positive effect to earning response coefficient (2) Growth opportunity has effect to earning response coefficien). (3) Managerial ownership has positive effect to earning response coefficien). (4) Institutional ownership has positive effect to earning response coefficient. Simultaneously, CSR, growth opportunity, managerial ownership and institutional ownership has significant effect to earning response coefficient. The implication of the research results is that investors need to pay attention to corporate social responsibility, growth opportunities and company characteristics which are proven to be able to be used to determine the ups and downs of share price based on market reactions to company profit information.